2023
DOI: 10.3390/ijms24032130
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Functional Characterization of Stress Related Glyoxalase Genes in Brassica napus L.

Abstract: Rapeseed (Brassica napus L.) is not only one of the most important oil crops in the world, but it is also an important vegetable crop with a high value nutrients and metabolites. However, rapeseed is often severely damaged by adverse stresses, such as low temperature, pathogen infection and so on. Glyoxalase I (GLYI) and glyoxalase II (GLYII) are two enzymes responsible for the detoxification of a cytotoxic metabolite methylglyoxal (MG) into the nontoxic S-D-lactoylglutathione, which plays crucial roles in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Furthermore, the gene duplication events analysis of AsGLX1 , AsGLX2 , and AsGLX3 genes showed that only AsGLX1 and AsGLX3 gene families had tandem duplications, while none of the three families had segmental duplications. In contrast, in O. sativa , Arabidopsis , B. napus and G. max , gene duplications of GLX1 and GLX2 genes were caused by the segmental duplication, rather than tandem duplication ( Mustafiz et al., 2011 ; Ghosh and Islam, 2016 ; Yan et al., 2023 ). Therefore, there are significant differences in gene duplication events that occur in the glyoxalase families in different plant species.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the gene duplication events analysis of AsGLX1 , AsGLX2 , and AsGLX3 genes showed that only AsGLX1 and AsGLX3 gene families had tandem duplications, while none of the three families had segmental duplications. In contrast, in O. sativa , Arabidopsis , B. napus and G. max , gene duplications of GLX1 and GLX2 genes were caused by the segmental duplication, rather than tandem duplication ( Mustafiz et al., 2011 ; Ghosh and Islam, 2016 ; Yan et al., 2023 ). Therefore, there are significant differences in gene duplication events that occur in the glyoxalase families in different plant species.…”
Section: Discussionmentioning
confidence: 94%
“…The identification and functional analysis of the glyoxalase gene family members have gained significant attention due to the diverse functions of glyoxalase enzymes. Although GLX1 and GLX2 genes have been genome-wide identified in model plants and important crops, such as Arabidopsis ( Mustafiz et al., 2011 ), O. sativa ( Mustafiz et al., 2011 ), Sorghum bicolor ( Bhowal et al., 2020 ), Glycine max ( Ghosh and Islam, 2016 ), and Brassica rapa ( Yan et al., 2018 ), the genome-wide identification on GLX3 is limited ( Li et al., 2019 ; Jana et al., 2021 ; Yan et al., 2023 ). Notably, both GLX1 and GLX2 genes in these species have multiple members with diverse subcellular localizations ( Li, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neighbor-Joining (NJ) phylogenetic tree was constructed by MEGA7.0 [ 20 ]. Bootstrap analysis was conducted with 1000 replications [ 21 ]. Then the evolutionary tree was visualized by using the online website iTOL ( https://itol.embl.de/ ).…”
Section: Methodsmentioning
confidence: 99%
“…The raw RNA sequencing data were filtered by a Perl script following the steps of the published work (Wu et al 2016) and our previous study (Khattak et al 2019, Wan et al 2023). DESeq2 v1.6.3 was used for differential gene expression analysis between different samples with three biological replicates under the theoretical basis obeys the hypothesis of the negative binomial distribution for the count value.…”
Section: Data Analysis and Differential Expression Gene Identificationmentioning
confidence: 99%